Aplicaciones cosméticas y estéticas del ácido hialurónico (2024)
This project aimed at the exhaustive compilation and consolidation of information on the cosmetic and aesthetic applications of hyaluronic acid in America and Europe during the last two decades. Its versatility, ability to provide volume, and maintain skin hydration have boosted its use as the most popular injectable filler in aesthetic medicine, covering a wide range of applications as topical products and facial and body dermal fillers. Through the review of databases such as Nature, Science Direct, Latindex, Oxford Academic, and Sage Journals, 7863 articles were collected, from which 60 were selected, meeting the required selection criteria. The information obtained was classified into general categories covering the lower third, middle third, upper third, body, comprehensive facial treatment, topical application, and complementary articles. This allowed addressing the generalities, applications, safety profiles, benefits, and potential complications of hyaluronic acid use. The reviewed studies confirm that hyaluronic acid offers a non-invasive alternative to traditional surgical methods, with reduced recovery times and adaptability to the anatomical characteristics of each patient. Regarding complications, it was found that, despite its high safety profile, mild complications such as swelling, bruising, and redness have been reported, as well as some more serious ones like vascular occlusions, granulomas, and infections which, although rare, require attention to prevent or treat them promptly.